Prospective Natural History Study in 24 Adult Patients With LGMDR12 Over 2 Years of Follow-up: Quantitative MRI and Clinical Outcome Measures. (9th August 2022) - De Wel, Bram; Huysmans, Lotte; Peeters, Ronald; Goosens, Veerle; Ghysels, Stefan; Byloos, Kris; Putzeys, Guido; D'Hondt, Ann; De Bleecker, Jan L.; Dupont, Patrick; Maes, Frederik; Claeys, Kristl G.
Abstract : Background and Objectives: Limb-girdle muscular dystrophy autosomal recessive type 12 (LGMDR12) is a rare hereditary muscular dystrophy for which outcome measures are currently lacking. We evaluated quantitative MRI and clinical outcome measures to track disease progression to determine which tests could be useful in future clinical trials to evaluate potential therapies. Methods: We prospectively measured the following outcome measures in all participants at baseline and after 1 and 2 years: 6-minute walk distance (6MWD), 10-meter walk test (10MWT), the Medical Research Council (MRC) sum scores, Biodex isometric dynamometry, serum creatine kinase, and 6-point Dixon MRI of the thighs. Results: We included 24 genetically confirmed, adult patients with LGMDR12 and 24 age-matched and sex-matched healthy controls. Patients with intermediate-stage thigh muscle fat replacement at baseline (proton density fat fraction [PDFF] 20%–70%) already showed an increase in PDFF in 8 of the 14 evaluated thigh muscles after 1 year. The standardized response mean demonstrated a high responsiveness to change in PDFF for 6 individual muscles over 2 years in this group. However, in patients with early-stage (<20%) or end-stage (>70%) muscle fat replacement, PDFF did not increase significantly over 2 years of follow-up. Biodex isometric dynamometry showed a significant decrease in muscle strength in all patients in the right and left hamstrings (−6.2 Nm, p < 0.002 and −4.6 Nm, p < 0.009, respectively) and right quadriceps muscles (−9 Nm, p = 0.044) after 1 year of follow-up, whereas the 6MWD, 10MWT, and MRC sum scores were not able to detect a significant decrease in muscle function/strength even after 2 years. There was a moderately strong correlation between total thigh PDFF and clinical outcome measures at baseline. Discussion: Thigh muscle PDFF imaging is a sensitive outcome measure to track progressive muscle fat replacement in selected patients with LGMDR12 even after 1 year of follow-up and correlates with clinical outcome measures. Biodex isometric dynamometry can reliably capture the loss of muscle strength over the course of 1 year in patients with LGMDR12 and should be included as an outcome measure in future clinical trials as well.